The influences of transformational leadership on employee employability: Evidence from China. Issue 1 (25th October 2018) - Yizhong, Xie; Baranchenko, Yevhen; Lin, Zhibin; Lau, Chi Keung; Ma, Jie
Abstract : Purpose: The purpose of this paper is to examine the mediating role of job characteristics and social exchange in transformational leadership (TFL) and employability relationship. Design/methodology/approach: The sample is composed of 760 participants employed in Yangtze Delta and Pearl River Delta in China. The participants have worked under their line manager for more than one year. In order to better prevent data from possible common method bias, two waves of surveys (in 2014) on a stratified sample, included a mix of industries, such as construction, manufacturing, finance, insurance and communications, were used to investigate the proposed relationship between TFL, job characteristics, social exchange and employability. Findings: The research has empirically tested the relationship between TFL and employability. While previous research has analyzed the relationship between them, the authors have enriched existing literature by exploring the mediating factors and illustrating the importance of indirect effects. Besides the direct effect, the results of this study showed that TFL could also improve employees' employability through job demands, skill discretion, decision authority, perceived organizational support and team–member exchange, but not leader–member exchange. Originality/value: The study opens up a debate around the employability of employees as it stands apart from the performance measurement. The authors believe that this new mediating model can provide an insight into complex mechanisms of employability enhancement from the perspective of leader development.